SCR denitration catalyst end hardening liquid and hardening method thereof
By using the end hardening liquid of the SCR denitrification catalyst, the structural strength and wear resistance of the catalyst are enhanced, and the problems of catalyst wear and collapse are solved, the service life is extended and efficient denitrification activity is maintained.
Patent Information
- Application Number
- CN202411352813.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-02-14
AI Technical Summary
Existing SCR denitrification catalysts are susceptible to excessive wear and collapse during use, resulting in a decrease in denitrification activity and a shortened service life.
Provide a SCR denitrification catalyst end hardening liquid containing active components, binders, dispersion stabilizers, hardeners and water. Through impregnation, curing and calcining, the end structural strength and wear resistance of the catalyst are enhanced. .
On the basis of maintaining the denitrification activity of the catalyst, the wear resistance of the catalyst is significantly improved and its service life is extended. The method is easy to operate and is easy to industrially apply.
Smart Images

Figure BDA0005062795740000141 
Figure BDA0005062795740000151
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of air pollution control, and in particular to an SCR denitration catalyst end hardening liquid and a hardening method thereof. Background Art
[0002] Nitrogen oxides (NO x ) is one of the main air pollutants, which not only threatens human health, but is also the main cause of haze, acid rain and photochemical smog. x In the technical field, the selective catalytic reduction method has been widely used due to its advantages such as high reliability, no by-products, and simple system installation.
[0003] At present, in the flue gas denitrification system of coal-fired power plants, the most widely used is a metal oxide catalyst that uses anatase-type titanium dioxide as a carrier to load vanadium oxide as an active substance, supplemented by tungsten oxide or molybdenum oxide as a co-catalyst. The most critical core of SCR denitrification technology is the catalyst. The quality of the catalyst directly determines the denitrification effect and service life of the SCR system. At present, there are two main factors affecting the service life of the catalyst: (1) Catalyst deactivation caused by catalyst poisoning, which in turn affects the service life of the catalyst; (2) Catalyst loss caused by excessive catalyst wear and collapse, which in turn affects the service life of the catalyst. At present, the selective catalytic reduction (SCR) flue gas denitrification process is the mainstream technology for denitrification, with a market share of about 95%. Among them, the catalyst is the core of SCR denitrification technology, but it is easily affected by the process layout location and coal quality, which can easily cause excessive wear of the catalyst, and even cause catalyst collapse in severe cases, resulting in a decrease in SCR denitrification activity and a shortened service life.
[0004] Therefore, developing how to enhance the wear resistance of the honeycomb SCR denitrification catalyst while maintaining a high denitrification activity is of great guiding significance for extending the service life of the catalyst and reducing environmental problems. Summary of the invention
[0005] The purpose of the present invention is to overcome the problem in the prior art that the catalyst is easily excessively worn during the SCR denitration process, and even causes the catalyst to collapse in severe cases, resulting in a decrease in the SCR denitration activity and a shortened service life. An SCR denitration catalyst end hardening liquid and a hardening method thereof are provided. This technical solution can greatly improve the structural strength and wear resistance of the end of the honeycomb SCR denitration catalyst module while maintaining the denitration activity, thereby effectively extending the overall service life of the catalyst.
[0006] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides an SCR denitration catalyst end curing liquid, which contains an active component, a binder, a dispersing stabilizer, a hardener and water. Based on the total weight of the SCR denitration catalyst end curing liquid, the content of the active component is 0.2-8wt%, the content of the binder is 1-15wt%, the content of the dispersing stabilizer is 2-35wt%, the content of the hardener is 3-40wt%, and the content of water is 2-93.8wt%; wherein the active component is a combination of ammonium metavanadate and ammonium heptamolybdate and / or vanadium sulfate, and the weight of the ammonium metavanadate accounts for 35-80% of the total weight of the active component; the hardener is at least two of aluminum sulfate, aluminum dihydrogen phosphate, zinc oxide, sodium borate and sodium silicate.
[0007] Preferably, the weight of the ammonium metavanadate accounts for 45-70% of the total weight of the active components, and more preferably 55-65%.
[0008] Preferably, based on the total weight of the SCR denitration catalyst end hardening liquid, the content of the active component is 0.5-5wt%, the content of the binder is 3-7wt%, the content of the dispersion stabilizer is 10-25wt%, the content of the hardener is 10-30wt%, and the content of water is 33-76.5wt%.
[0009] Preferably, the hardener is a combination of aluminum sulfate and aluminum dihydrogen phosphate, and the weight ratio of aluminum sulfate to aluminum dihydrogen phosphate is (2-9):1.
[0010] Preferably, the binder is at least three of hydroxymethyl cellulose, hydroxypropyl methyl cellulose, hydroxypropyl cellulose, polyethylene oxide, polydimethylsiloxane and polyvinyl alcohol.
[0011] Preferably, the binder is a combination of hydroxymethyl cellulose, hydroxypropyl methyl cellulose and hydroxypropyl cellulose, and the weight ratio of hydroxymethyl cellulose, hydroxypropyl methyl cellulose and hydroxypropyl cellulose is (0.6-1.5):(0.6-1.5):1.
[0012] Preferably, the dispersion stabilizer is at least one of borax, pyrolusite, sulfuric acid and phosphoric acid.
[0013] A second aspect of the present invention provides a method for hardening an end portion of an SCR denitration catalyst, the method comprising:
[0014] Prepare the above-mentioned SCR denitration catalyst end curing liquid; immerse the axial end face of the SCR denitration catalyst module in the SCR denitration catalyst end curing liquid, and then perform curing and calcination in sequence.
[0015] Preferably, the length of the axial end surface of the denitration catalyst module is 5-20 cm; and the immersion time is 5-120 s.
[0016] Preferably, the curing conditions include: temperature of 10-35° C., humidity of 20-80%, and time of 2-60 hours.
[0017] Preferably, the calcination conditions include: temperature of 80-400° C. and time of 0.5-6 h.
[0018] Through the above technical solution, the wear resistance of the SCR denitration catalyst can be effectively and significantly enhanced, and the SCR denitration catalyst can still maintain a high denitration activity, effectively extending the overall service life of the catalyst. In addition, the method for hardening the end of the SCR denitration catalyst of the present invention is easy to operate and easy to industrialize. DETAILED DESCRIPTION
[0019] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0020] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0021] The SCR denitration catalyst end hardening liquid of the present invention contains active components, binders, dispersing stabilizers, hardeners and water. Based on the total weight of the SCR denitration catalyst end hardening liquid, the content of the active components is 0.2-8wt%, the content of the binder is 1-15wt%, the content of the dispersing stabilizer is 2-35wt%, the content of the hardener is 3-40wt%, and the content of water is 2-93.8wt%; wherein the active component is a combination of ammonium metavanadate and ammonium heptamolybdate and / or vanadyl sulfate, and the weight of the ammonium metavanadate accounts for 35-80% of the total weight of the active components; the hardener is at least two of aluminum sulfate, aluminum dihydrogen phosphate, zinc oxide, sodium borate and sodium silicate. According to the SCR denitration catalyst end hardening liquid of the present invention, the honeycomb SCR denitration catalyst module can greatly improve the structural strength and wear resistance of its end while maintaining the denitration activity, and effectively extend the overall service life of the catalyst.
[0022] In the SCR denitration catalyst end hardening liquid described in the present invention, in order to improve the structural strength and wear resistance of the SCR denitration catalyst end, the weight of the ammonium metavanadate accounts for 45-70% of the total weight of the active component, and more preferably 55-65%. For example, it can be 45%, 48%, 50%, 52%, 55%, 58%, 60%, 62%, 65%, 68% or 70%.
[0023] In some embodiments, the active components are ammonium metavanadate and ammonium heptamolybdate, and the weight of the ammonium metavanadate accounts for 35-80% of the total weight of the active components. In other embodiments, the active components are ammonium metavanadate and vanadyl sulfate, and the weight of the ammonium metavanadate accounts for 35-80% of the total weight of the active components. In other embodiments, the active components are ammonium metavanadate, ammonium heptamolybdate and vanadyl sulfate, and the weight of the ammonium metavanadate accounts for 35-80% of the total weight of the active components.
[0024] In the SCR denitration catalyst end hardening liquid described in the present invention, in order to improve the wear resistance of the SCR denitration catalyst, based on the total weight of the SCR denitration catalyst end hardening liquid, the content of the active component is preferably 0.5-5wt%, the content of the binder is preferably 3-7wt%, the content of the dispersion stabilizer is preferably 10-25wt%, the content of the hardener is preferably 10-30wt%, and the content of water is preferably 33-76.5wt%.
[0025] In the SCR denitration catalyst end hardening liquid described in the present invention, in order to improve the wear resistance of the SCR denitration catalyst, the hardener is preferably a combination of aluminum sulfate and aluminum dihydrogen phosphate, and the weight ratio of aluminum sulfate to aluminum dihydrogen phosphate is preferably (2-9):1, specifically, for example, 2:1, 5:2, 3:1, 4:1, 5:1, 6:1, 7:1, 15:2, 8:1 or 9:1.
[0026] In the SCR denitration catalyst end hardening liquid of the present invention, in order to improve the mechanical strength and structural stability of the SCR denitration catalyst, the binder is preferably at least three of hydroxymethyl cellulose, hydroxypropyl methyl cellulose, hydroxypropyl cellulose, polyethylene oxide, polydimethylsiloxane and polyvinyl alcohol. In a more preferred case, the binder is a combination of hydroxymethyl cellulose, hydroxypropyl methyl cellulose and hydroxypropyl cellulose, and the weight ratio of hydroxymethyl cellulose, hydroxypropyl methyl cellulose and hydroxypropyl cellulose is (0.6-1.5): (0.6-1.5): 1, specifically, for example, 0.6: 0.6: 1, 1: 1: 1, 1.2: 1.2: 1, 1.3: 1.3: 1, 1.4: 1.4: 1 or 1.5: 1.5: 1.
[0027] In the SCR denitration catalyst end hardening liquid of the present invention, the dispersion stabilizer can be at least one of pyrolusite, sulfuric acid and phosphoric acid. In a preferred case, the dispersion stabilizer is phosphoric acid and sulfuric acid, and the weight ratio of phosphoric acid to sulfuric acid is (1-2):1, specifically, for example, 1:1, 1.5:1 or 2:1. The concentration of the sulfuric acid can be 5-30wt%, preferably 10-25wt%. The concentration of the phosphoric acid can be 5-30wt%, preferably 10-25wt%.
[0028] In some embodiments, the SCR denitration catalyst end hardening liquid of the present invention contains active components, binders, dispersing stabilizers, hardeners and water. Based on the total weight of the SCR denitration catalyst end hardening liquid, the content of the active components is 0.2-8wt%, the content of the binders is 1-15wt%, the content of the dispersing stabilizers is 2-35wt%, the content of the hardeners is 3-40wt%, and the content of water is 2-93.8wt%; wherein the active component is a combination of ammonium metavanadate and ammonium heptamolybdate and / or vanadium sulfate, and the weight of the ammonium metavanadate accounts for 35-80% of the total weight of the active components; the hardener is at least two of aluminum sulfate, aluminum dihydrogen phosphate, zinc oxide, sodium borate and sodium silicate; the binder is at least three of hydroxymethyl cellulose, hydroxypropyl methyl cellulose, hydroxypropyl cellulose, polyethylene oxide, polydimethylsiloxane and polyvinyl alcohol; the dispersing stabilizer is at least one of borax, pyrolusite, sulfuric acid and phosphoric acid. The concentration of sulfuric acid is 5-30wt%. The concentration of the phosphoric acid is 5-30 wt %.
[0029] In other embodiments, the SCR denitration catalyst end curing liquid of the present invention contains an active component, a binder, a dispersing stabilizer, a hardener and water. Based on the total weight of the SCR denitration catalyst end curing liquid, the content of the active component is 0.5-5wt%, the content of the binder is 3-7wt%, the content of the dispersing stabilizer is 10-25wt%, the content of the hardener is 10-30wt%, and the content of water is 33-76.5wt%; wherein the active component is a combination of ammonium metavanadate and ammonium heptamolybdate, and the metavanadate is 0.5-5wt%. The weight of ammonium vanadate accounts for 45-70% of the total weight of the active components; the hardener is a combination of aluminum sulfate and aluminum dihydrogen phosphate, and the weight ratio of aluminum sulfate to aluminum dihydrogen phosphate is (2-9):1; the binder is a combination of hydroxymethyl cellulose, hydroxypropyl methyl cellulose and hydroxypropyl cellulose, and the weight ratio of hydroxymethyl cellulose, hydroxypropyl methyl cellulose and hydroxypropyl cellulose is (0.6-1.5):(0.6-1.5):1; the dispersion stabilizer is a combination of borax and sulfuric acid, and the weight ratio of borax to sulfuric acid is (0.5-1.7):1. The concentration of the sulfuric acid is 5-30wt%.
[0030] The present invention also provides a method for hardening the end of an SCR denitration catalyst, the method comprising:
[0031] Prepare the above-mentioned SCR denitration catalyst end curing liquid; immerse the axial end face of the SCR denitration catalyst module in the SCR denitration catalyst end curing liquid, and then perform curing and calcination in sequence.
[0032] According to the method described in the present invention, the wear resistance of the SCR denitration catalyst can be effectively and significantly enhanced, and the SCR denitration catalyst can still maintain a relatively high denitration activity; and the method described in the present invention is easy to operate and is easy to industrially apply.
[0033] In the method of the present invention, the specific process of preparing the above-mentioned SCR denitration catalyst end hardening liquid may include: stirring and mixing the SCR denitration catalyst end hardening liquid according to the SCR denitration catalyst end hardening liquid of the present invention. The stirring and mixing conditions include: the temperature may be 20-100°C, preferably 35-65°C; the stirring rate may be 200-700rpm, preferably 450-650rpm; the time may be 1-10h, preferably 2.5-4.5h.
[0034] In the method of the present invention, the length of the axial end surface of the denitration catalyst module may be 5-20 cm, preferably 10-15 cm; the immersion time may be 5-120 s, preferably 10-100 s, more preferably 15-60 s.
[0035] In the method described in the present invention, the curing conditions include: the temperature can be 10-35°C, preferably 15-25°C, and specifically for example can be 10°C, 12°C, 15°C, 18°C, 20°C, 22°C, 25°C, 28°C, 30°C, 32°C or 35°C; the humidity can be 20-80%, preferably 30-60%, and specifically for example can be 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or 80%; the time can be 2-60h, preferably 5-40h, and more preferably 10-30h.
[0036] In the method described in the present invention, the calcination conditions include: the temperature can be 80-400°C, preferably 100-300°C, for example, it can be 80°C, 100°C, 120°C, 150°C, 180°C, 200°C, 220°C, 250°C, 280°C, 300°C, 320°C, 350°C, 380°C or 400°C; the time can be 0.5-6h, preferably 1-4h, more preferably 2-3h.
[0037] In some embodiments, the method for hardening the end of the SCR denitration catalyst of the present invention comprises:
[0038] Prepare the above-mentioned SCR denitration catalyst end hardening liquid; immerse the axial end face of the SCR denitration catalyst module at 5-20 cm in the SCR denitration catalyst end hardening liquid for 5-120 seconds, and then successively perform curing at a temperature of 10-35°C and a humidity of 20-80% for 2-60 hours and calcining at a temperature of 80-400°C for 0.5-6 hours.
[0039] In other embodiments, the method for hardening the end of the SCR denitration catalyst of the present invention comprises:
[0040] Prepare the above-mentioned SCR denitration catalyst end hardening liquid; immerse the axial end face of the SCR denitration catalyst module at 10-15 cm in the SCR denitration catalyst end hardening liquid for 10-100 seconds, and then successively perform curing at a temperature of 15-25°C and a humidity of 30-60% for 5-40 hours and calcining at a temperature of 100-300°C for 1-4 hours.
[0041] The SCR denitration catalyst end hardening liquid and hardening method of the present invention are further described below by examples. The examples are implemented based on the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following examples.
[0042] The experimental methods in the following examples are conventional methods in the art unless otherwise specified. The experimental materials used in the following examples are all commercially available unless otherwise specified; sulfuric acid, aluminum dihydrogen phosphate, hydroxypropyl methylcellulose, hydroxypropyl cellulose, polyethylene oxide, hydroxymethyl cellulose, sodium borate, and ammonium heptamolybdate used in the experiment are all Chinese medicine analytical pure reagents; the ammonium metavanadate used is an industrial grade product produced by Nanyang Handing High-tech Materials Co., Ltd.; aluminum sulfate is an industrial grade product produced by Zibo Shuangying New Materials Technology Co., Ltd.
[0043] Example 1
[0044] 3g of ammonium metavanadate, 2g of ammonium heptamolybdate, 3g of sulfuric acid with a concentration of 20wt%, 1.5g of hydroxymethylcellulose, 1.5g of hydroxypropylmethylcellulose, 1.5g of hydroxypropylcellulose, 1.5g of polyethylene oxide, 5g of aluminum sulfate and 2g of aluminum dihydrogen phosphate were dissolved in 79g of deionized water and stirred for 3h at a temperature of 45°C and a stirring rate of 600rpm to obtain an SCR denitration catalyst end hardening liquid; the axial end face of the SCR denitration catalyst module at 10cm was immersed in the SCR denitration catalyst end hardening liquid for 50s, and then cured for 12h at a temperature of 20°C and a humidity of 40% and calcined in a roasting furnace at a temperature of 200°C for 2h. The mass proportions of active components, binders, dispersing stabilizers and hardeners in the SCR denitration catalyst end hardening liquid and the mass proportion of the weight of ammonium metavanadate in the active components are recorded in Table 1.
[0045] Example 2
[0046] 3g of ammonium metavanadate, 2g of ammonium heptamolybdate, 3g of sulfuric acid with a concentration of 20wt%, 1.5g of hydroxymethylcellulose, 1.5g of hydroxypropylmethylcellulose, 1.5g of hydroxypropylcellulose, 1.5g of polyethylene oxide, 5g of sodium borate, 5g of aluminum sulfate and 2g of aluminum dihydrogen phosphate were dissolved in 74g of deionized water and stirred and mixed for 3h at a temperature of 45°C and a stirring rate of 600rpm to obtain an SCR denitration catalyst end hardening liquid; the axial end face of the SCR denitration catalyst module at 10cm was immersed in the SCR denitration catalyst end hardening liquid for 50s, and then cured for 12h at a temperature of 20°C and a humidity of 40% and calcined in a roasting furnace at a temperature of 200°C for 2h. The mass proportions of active components, binders, dispersing stabilizers and hardeners in the SCR denitration catalyst end hardening liquid and the mass proportion of the weight of ammonium metavanadate in the active components are recorded in Table 1.
[0047] Example 3
[0048] 3g of ammonium metavanadate, 2g of ammonium heptamolybdate, 5g of sodium borate, 3g of sulfuric acid with a concentration of 20wt%, 1g of hydroxymethylcellulose, 1g of hydroxypropylmethylcellulose, 1g of hydroxypropylcellulose, 15g of aluminum sulfate and 2g of aluminum dihydrogen phosphate were dissolved in 67g of deionized water and stirred and mixed for 3h at a temperature of 45°C and a stirring rate of 600rpm to obtain an SCR denitration catalyst end hardening liquid; the axial end face of the SCR denitration catalyst module at 10cm was immersed in the SCR denitration catalyst end hardening liquid for 50s, and then cured for 12h at a temperature of 20°C and a humidity of 40% and calcined in a roasting furnace at a temperature of 200°C for 2h. The mass proportions of active components, binders, dispersing stabilizers and hardeners in the SCR denitration catalyst end hardening liquid and the mass proportion of the weight of ammonium metavanadate in the active components are recorded in Table 1.
[0049] Example 4
[0050] 2.1g ammonium metavanadate, 0.9g ammonium heptamolybdate, 3g borax, 6g sulfuric acid with a concentration of 10wt%, 0.8g hydroxymethyl cellulose, 0.8g hydroxypropyl methyl cellulose, 1.4g hydroxypropyl cellulose, 9g aluminum sulfate and 1g aluminum dihydrogen phosphate were dissolved in 75g deionized water and stirred for 3h at a temperature of 45°C and a stirring rate of 600rpm to obtain an SCR denitration catalyst end hardening liquid; the axial end face of the SCR denitration catalyst module at 10cm was immersed in the SCR denitration catalyst end hardening liquid for 50s, and then cured for 12h at a temperature of 20°C and a humidity of 40% and calcined in a roasting furnace at a temperature of 200°C for 2h. The mass proportions of active components, binders, dispersing stabilizers and hardeners in the SCR denitration catalyst end hardening liquid and the mass proportion of the weight of ammonium metavanadate in the active components are recorded in Table 1.
[0051] Example 5
[0052] 0.225g of ammonium metavanadate, 0.275g of ammonium heptamolybdate, 3.5g of borax, 6.5g of sulfuric acid with a concentration of 20wt%, 1g of hydroxymethylcellulose, 1g of hydroxypropylmethylcellulose, 1g of hydroxypropylcellulose, 6.5g of aluminum sulfate and 3.5g of aluminum dihydrogen phosphate were dissolved in 76.5g of deionized water and stirred and mixed for 3h at a temperature of 45°C and a stirring rate of 600rpm to obtain an SCR denitration catalyst end hardening liquid; the axial end face of the SCR denitration catalyst module at 10cm was immersed in the SCR denitration catalyst end hardening liquid for 50s, and then cured for 12h at a temperature of 20°C and a humidity of 40% and calcined in a roasting furnace at a temperature of 200°C for 2h. The mass proportions of active components, binders, dispersing stabilizers and hardeners in the SCR denitration catalyst end hardening liquid and the mass proportion of the weight of ammonium metavanadate in the active components are recorded in Table 1.
[0053] Example 6
[0054] 3g of ammonium metavanadate, 2g of ammonium heptamolybdate, 1g of borax, 10g of sulfuric acid with a concentration of 5wt%, 2.6g of hydroxymethylcellulose, 2.6g of hydroxypropylmethylcellulose, 1.8g of hydroxypropylcellulose, 20g of aluminum sulfate and 10g of aluminum dihydrogen phosphate were dissolved in 47g of deionized water and stirred for 3h at a temperature of 45°C and a stirring rate of 600rpm to obtain an SCR denitration catalyst end hardening liquid; the axial end face of the SCR denitration catalyst module at 10cm was immersed in the SCR denitration catalyst end hardening liquid for 50s, and then cured for 12h at a temperature of 20°C and a humidity of 40% and calcined in a roasting furnace at a temperature of 200°C for 2h. The mass proportions of active components, binders, dispersing stabilizers and hardeners in the SCR denitration catalyst end hardening liquid and the mass proportion of the weight of ammonium metavanadate in the active components are recorded in Table 1.
[0055] Example 7
[0056] 2.8g of ammonium metavanadate, 5.2g of vanadyl sulfate, 25g of pyrolusite, 10g of phosphoric acid with a concentration of 5wt%, 5g of polydimethylsiloxane, 5g of polyethylene oxide, 5g of polyvinyl alcohol, 30g of zinc oxide and 10g of sodium borate were dissolved in 2g of deionized water and stirred for 10h at a temperature of 20°C and a stirring rate of 200rpm to obtain an SCR denitration catalyst end curing liquid; the axial end face of the SCR denitration catalyst module at 10cm was immersed in the SCR denitration catalyst end curing liquid for 50s, and then cured for 12h at a temperature of 20°C and a humidity of 40% and calcined in a roasting furnace at a temperature of 200°C for 2h. The mass proportions of active components, binders, dispersing stabilizers and curing agents in the SCR denitration catalyst end curing liquid and the mass proportion of the weight of ammonium metavanadate in the active components are recorded in Table 1.
[0057] Example 8
[0058] 0.16g of ammonium metavanadate, 0.04g of vanadyl sulfate, 1g of pyrolusite, 1g of phosphoric acid with a concentration of 30wt%, 0.3g of polyethylene oxide, 0.3g of polydimethylsiloxane, 0.4g of hydroxypropyl cellulose, 2g of sodium borate and 1g of sodium silicate were dissolved in 2g of deionized water and stirred for 1h at a temperature of 100°C and a stirring rate of 700rpm to obtain an SCR denitration catalyst end hardening liquid; the axial end face of the SCR denitration catalyst module at 10cm was immersed in the SCR denitration catalyst end hardening liquid for 50s, and then cured for 12h at a temperature of 20°C and a humidity of 40% and calcined in a roasting furnace at a temperature of 200°C for 2h. The mass proportions of active components, binders, dispersing stabilizers and hardeners in the SCR denitration catalyst end hardening liquid and the mass proportion of the weight of ammonium metavanadate in the active components are recorded in Table 1.
[0059] Example 9
[0060] 3g of ammonium metavanadate, 2g of ammonium heptamolybdate, 5g of borax, 3g of sulfuric acid with a concentration of 30wt%, 1g of hydroxymethylcellulose, 1g of hydroxypropylmethylcellulose, 1g of hydroxypropylcellulose, 15g of aluminum sulfate and 2g of aluminum dihydrogen phosphate were dissolved in 67g of deionized water and stirred and mixed for 3h at a temperature of 45°C and a stirring rate of 600rpm to obtain an SCR denitration catalyst end hardening liquid; the axial end face of the SCR denitration catalyst module at 5cm was immersed in the SCR denitration catalyst end hardening liquid for 10s, and then cured for 5h at a temperature of 15°C and a humidity of 30% and calcined in a roasting furnace at a temperature of 100°C for 1h. The mass proportions of active components, binders, dispersing stabilizers and hardeners in the SCR denitration catalyst end hardening liquid and the mass proportion of the weight of ammonium metavanadate in the active components are recorded in Table 1.
[0061] Example 10
[0062] 3g of ammonium metavanadate, 2g of ammonium heptamolybdate, 5g of borax, 3g of sulfuric acid with a concentration of 30wt%, 1g of hydroxymethylcellulose, 1g of hydroxypropylmethylcellulose, 1g of hydroxypropylcellulose, 15g of aluminum sulfate and 2g of aluminum dihydrogen phosphate were dissolved in 67g of deionized water and stirred and mixed for 3h at a temperature of 45°C and a stirring rate of 600rpm to obtain an SCR denitration catalyst end hardening liquid; the axial end face of the SCR denitration catalyst module at 5cm was immersed in the SCR denitration catalyst end hardening liquid for 100s, and then cured for 40h at a temperature of 25°C and a humidity of 60% and calcined in a roasting furnace at a temperature of 300°C for 4h. The mass proportions of active components, binders, dispersing stabilizers and hardeners in the SCR denitration catalyst end hardening liquid and the mass proportion of the weight of ammonium metavanadate in the active components are recorded in Table 1.
[0063] Embodiment 11
[0064] 3g of ammonium metavanadate, 2g of ammonium heptamolybdate, 5g of borax, 3g of sulfuric acid with a concentration of 5wt%, 1g of hydroxymethylcellulose, 1g of hydroxypropylmethylcellulose, 1g of hydroxypropylcellulose, 15g of aluminum sulfate and 2g of aluminum dihydrogen phosphate were dissolved in 67g of deionized water and stirred and mixed for 3h at a temperature of 45°C and a stirring rate of 600rpm to obtain an SCR denitration catalyst end hardening liquid; the axial end face of the SCR denitration catalyst module at 5cm was immersed in the SCR denitration catalyst end hardening liquid for 5s, and then cured for 2h at a temperature of 10°C and a humidity of 30% and calcined in a roasting furnace at a temperature of 80°C for 0.5h. The mass proportions of active components, binders, dispersing stabilizers and hardeners in the SCR denitration catalyst end hardening liquid and the mass proportion of the weight of ammonium metavanadate in the active components are recorded in Table 1.
[0065] Example 12
[0066] 3g of ammonium metavanadate, 2g of ammonium heptamolybdate, 5g of borax, 3g of sulfuric acid with a concentration of 20wt%, 1g of hydroxymethylcellulose, 1g of hydroxypropylmethylcellulose, 1g of hydroxypropylcellulose, 15g of aluminum sulfate and 2g of aluminum dihydrogen phosphate were dissolved in 67g of deionized water and stirred and mixed for 3h at a temperature of 45°C and a stirring rate of 600rpm to obtain an SCR denitration catalyst end hardening liquid; the axial end face 20cm of the SCR denitration catalyst module was immersed in the SCR denitration catalyst end hardening liquid for 50s, and then cured for 60h at a temperature of 35°C and a humidity of 60% and calcined in a roasting furnace at a temperature of 400°C for 6h. The mass proportions of active components, binders, dispersing stabilizers and hardeners in the SCR denitration catalyst end hardening liquid and the mass proportion of the weight of ammonium metavanadate in the active components are recorded in Table 1.
[0067] Comparative Example 1
[0068] The method of Example 3 was followed, except that the SCR denitration catalyst end hardening liquid was replaced by dissolving 4g of ammonium metavanadate, 6g of ammonium heptamolybdate, 3g of sulfuric acid with a concentration of 20wt%, 1g of hydroxymethyl cellulose, 1g of hydroxypropyl methylcellulose, 1g of hydroxypropyl cellulose, 15g of aluminum sulfate and 2g of aluminum dihydrogen phosphate in 67g of deionized water. The mass proportions of active components, binders, dispersing stabilizers and hardeners in the SCR denitration catalyst end hardening liquid and the mass proportion of the weight of ammonium metavanadate in the active components are recorded in Table 1.
[0069] Comparative Example 2
[0070] The method of Example 3 was followed, except that the SCR denitration catalyst end curing liquid was replaced with a conventional curing liquid (20 wt % aluminum sulfate solution), and no active component, binder, or dispersion stabilizer was added.
[0071] Test Case
[0072] The SCR denitration catalysts treated by the methods of Examples 1-12 and Comparative Examples 1-2 were subjected to wear tests. The test method was based on the national standard GB / T 31587-2015 "Honeycomb Flue Gas Denitration Catalysts". The wear rates were recorded in Table 1.
[0073] Activity test
[0074] The SCR denitration catalyst treated by the method of Example 3 was tested for catalyst denitration efficiency (activity). With reference to the national standard GB / T 31587-2015 "Honeycomb Flue Gas Denitration Catalyst", the denitration activity K value was measured to be 42.5 m / h.
[0075] Table 1
[0076]
[0077]
[0078] It can be seen from the results in Table 1 that the SCR denitration catalyst treated by the embodiment of the method described in the present invention has a lower wear rate, which greatly improves the structural strength and wear resistance of its end.
[0079] It can be seen from the results of the stability test that the SCR denitration catalyst treated by the embodiment of the method described in the present invention has a prolonged service life.
[0080] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A SCR denitration catalyst end hardening liquid, characterized in that: The SCR denitration catalyst end hardening liquid contains active components, a binder, a dispersing stabilizer, a hardener and water. Based on the total weight of the SCR denitration catalyst end hardening liquid, the content of the active components is 0.2-8wt%, the content of the binder is 1-15wt%, the content of the dispersing stabilizer is 2-35wt%, the content of the hardener is 3-40wt%, and the content of water is 2-93.8wt%; Wherein, the active component is a combination of ammonium metavanadate and ammonium heptamolybdate and / or vanadyl sulfate, and the weight of the ammonium metavanadate accounts for 35-80% of the total weight of the active components; The hardener is at least two of aluminum sulfate, aluminum dihydrogen phosphate, zinc oxide, sodium borate and sodium silicate.
2. The SCR denitration catalyst end hardening liquid according to claim 1, characterized in that: The weight of the ammonium metavanadate accounts for 45-70% of the total weight of the active components, and more preferably 55-65%.
3. The SCR denitration catalyst end curing liquid according to claim 1 or 2, characterized in that: Based on the total weight of the SCR denitration catalyst end hardening liquid, the content of the active component is 0.5-5wt%, the content of the binder is 3-7wt%, the content of the dispersion stabilizer is 10-25wt%, the content of the hardener is 10-30wt%, and the content of water is 33-76.5wt%.
4. The SCR denitration catalyst end hardening liquid according to any one of claims 1 to 3, characterized in that: The hardener is a combination of aluminum sulfate and aluminum dihydrogen phosphate, and the weight ratio of aluminum sulfate to aluminum dihydrogen phosphate is (2-9):
1.
5. The SCR denitration catalyst end hardening liquid according to any one of claims 1 to 4, characterized in that: The binder is at least three of hydroxymethyl cellulose, hydroxypropyl methyl cellulose, hydroxypropyl cellulose, polyethylene oxide, polydimethylsiloxane and polyvinyl alcohol.
6. The SCR denitration catalyst end hardening liquid according to claim 5, characterized in that: The binder is a combination of hydroxymethyl cellulose, hydroxypropyl methyl cellulose and hydroxypropyl cellulose, and the weight ratio of hydroxymethyl cellulose, hydroxypropyl methyl cellulose and hydroxypropyl cellulose is (0.6-1.5):(0.6-1.5):
1.
7. The SCR denitration catalyst end hardening liquid according to any one of claims 1 to 6, characterized in that: The dispersion stabilizer is at least one of borax, pyrolusite, sulfuric acid and phosphoric acid.
8. A method for hardening the end of an SCR denitration catalyst, characterized in that: The method includes: Prepare the SCR denitration catalyst end hardening liquid according to any one of claims 1 to 7; The axial end face of the SCR denitration catalyst module is immersed in the SCR denitration catalyst end curing liquid, and then cured and calcined in sequence; Preferably, the length of the axial end surface of the denitration catalyst module is 5-20 cm; and the immersion time is 5-120 s.
9. The method according to claim 8, characterized in that The curing conditions include: temperature of 10-35° C., humidity of 20-80%, and time of 2-60 hours.
10. The method according to claim 8 or 9, characterized in that: The calcination conditions include: temperature of 80-400° C. and time of 0.5-6 h.